Segmen Berita Feature pada Program Berita Jawa Tengah Hari Ini di TVRI Stasiun Jawa Tengah - Ana Ahyana; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Television is a mass media which still becomes the most consumed media by the public. Various kinds of shows on television become daily consumption, including news. The news broadcasted must have high quality. It is not surprising that many television stations compete to make news programs with a wide variety of interesting, educative, entertaining and informative contents. One of them is Central Java Station TVRI, a national television station which also competes by conducting a rebranding program with the main goal targeting viewers from the millennial generation. Central Java Station TVRI in carrying out the rebranding program, presents and augments high quality programs and shows without leaving any informative elements behind. One of the shows attracting audience’s interest is feature news. The Journalism Field Work Team of the Communication Science Department, Universitas Diponegoro, presents a feature segment which will be broadcasted in Jawa Tengah Hari Ini news program. The feature news segment discusses several chosen themes following the majority of the audience taste, such as tourism, culinary, and also community (hobbies). There are 48 feature news segments which started to be aired from July 27, 2020 to November 2, 2020 with 3-5 minutes video duration. Related to the working process on this Field Work, the writer has done several job descriptions such as being a producer, a camera person, a reporter, a script writer, a voice over, and a video editor. The distribution of the job desk divided according to the theme of the coverage and writer has different tasks in each segment. During the working process on the feature news segment, there were several obstacles found by the writer and the team. Through this feature news segment, the writer and the whole team hope to present an informative and educative broadcast for the audience namely a feature news segment, and to provide solace for them during the Covid-19 Pandemic. The broadcast presented by the Journalism Field Work Team of the Communication Science Department, Universitas Diponegoro, is also expected to be one of the contributions from communication science students for the media and local television industry.